Hydroxychloroquine use in COVID-19: is the risk of cardiovascular toxicity justified?. Issue 2 (19th August 2020) - Stevenson, Alex; Kirresh, Ali; Conway, Samuel; White, Laura; Ahmad, Mahmood; Little, Callum
Abstract : The outbreak of COVID-19 in Wuhan, China and its declaration as a global pandemic by WHO has left the medical community under significant pressure to rapidly identify effective therapeutic and preventative strategies. Chloroquine (CQ) and its analogue hydroxychloroquine (HCQ) were found to be efficacious against SARS-CoV-2 when investigated in preliminary in vitro experiments. Reports of success in early clinical studies were widely publicised by news outlets, politicians and on social media. These results led several countries to approve the use of these drugs for the treatment of patients with COVID-19. Despite having reasonable safety profiles in the treatment of malaria and certain autoimmune conditions, both drugs are known to have potential cardiotoxic side effects. There is a high incidence of myocardial injury and arrhythmia reported with COVID-19 infection, and as such this population may be more susceptible to this side-effect profile. Studies to date have now demonstrated that in patients with COVID-19, these drugs are associated with significant QTc prolongation, as well as reports of ventricular arrhythmias. Furthermore, subsequent studies have failed to demonstrate clinical benefit from either drug. Indeed, clinical trials have also been stopped early due to safety concerns over HCQ. There is an urgent need for credible solutions to the global pandemic, but we argue that in the absence of high-quality evidence, there needs to be greater caution over the routine use or authorisation of drugs for which efficacy and safety is unproven.